The management of Premenstrual syndrome: A review (Bangladesh Journal of Medical Science, 2018)
Premenstrual Syndrome is a set of physical, emotional and behavioural symptoms that start during the week preceding menstruation and are alleviated when the menstrual flow begins. Epidemiological surveys have estimated that the frequency of PMS symptoms is about 80-90% with impairment of functioning. Women with severe PMS should be managed by a multi disciplinary team, which might comprise a hospital or community gynaecologist, psychiatrist or psychologist, dietician and counselor. Where there is multidisciplinary provision of care, this is of benefit both from the diagnostic and therapeutic point of view, giving the ability to offer a broad range of interventions from lifestyle interventions and cognitive behavioural therapy (CBT) to gynaecological interventions.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.16-20